Analisis Relasi Fenomena Kriminalitas Dengan Kebijakan Publik - Iwansyah, Henry (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study revealed the phenomenon of crime in North Lampung Regency, Lampung Province. The aim, in addition to getting a complete picture, is to analyze the relationship between empirical phenomena and local government policies. This type of research is